THE EFFECT OF HIGH LIPID DIET LIPOPOLYSACCHARIDE AND LAPARATOMY SURGERY ON THE LEVEL OF C-REACTIVE PROTEIN SERUM IN SPRAGUE DAWLEY RATS EKD - Dhirgo Adji (Jurnal Sain Veteriner, 2007)
C-reactive protein (CRP) is a member of the family of proteins known as pentraxins, and originally defined as a substance, observed in the serum or plasma of patient with acute infections, that reacted with the Cpolysaccharide of the pneumococcus. Serum concentrations of CRP increase as part of the inflammatory response to infection or acute injury. The aim of the study was to see the differences between acute and chronicstimuli in the increasing of CRP concentration in serum of Sprague Dawley rat. Twenty male Sprague Dawley rats, 1.5 months of age were used as experimental animals. Rats were adapted for 5 days and given basal diet,containing normal fat(5% of fat) and water ad libitum. Rats were then divided into 4 groups of 5 each. Group 1 was used as control animal. The animals in this group were fed basal diet for 59 days without any othertreatments. Group 2 was animals fed high fat diet containin g20Yo of fat, for 59 days without any other treatments. Group 3 was animals fed basal diet for 59 days and in the day of 60 then injected with LPS from Escherichia coli 0111:B4, 1 mg/kg BW intraperitoneally, and Group 4 was animals fed basal diet for 59 days and in the day of 60 animals then laparatomized. Twenty four hours after all treatments, blood sample were collected from orbitally vein, serum was separated and used to analyze CRP concentration. Statistical analyzes using onew ay analyzeso fvariances howed that there were significance differences among Group 1,2,3 and 4 (p<0.05). Mean of CRP concentrations respectively from the highest to the lowest were: Group 3, Group 4, Group 2 and Group 1. Fromthe result of the study it can be concluded that CRP concentration of acute stimulus was higher than chronic stimulus.Key words : C-reactivep rotein, lipopolysaccharides, high fat diet, laparatomy.